Analysis of Peak Discharge (Flood) in Tangi-E-Gharo Station - Reshteen, Sediqullah (Journal of Natural Sciences – Kabul University, 2021)
Flooding is a natural phenomenon with significant financial and life-threatening consequences. However, implementing precautionary measures can mitigate its negative effects and even prevent damages. Peak discharge, or flooding, occurs when the water volume in a river exceeds the riverbed's capacity, causing overflow onto surrounding lands. This situation can arise from excessive rainfall or rapid snowmelt due to sudden warming. Floodwaters may carry fertile soils into seas, resulting in both damage and potential agricultural benefits. This article analyzes the upstream flood flow in Tangi-e-Gharo station, considering trends and historical data to understand its characteristics and impacts.